Documents on and from the history of economic thought and methodology - Johnson, Marianne F.; Johnson, Kirk; Samuels, Warren J., 1933- (Emerald, 2008)
Volume 26C contains five sets of lectures taken by Glenn Johnson as a doctoral student in economics at the University of Chicago during 1946-7.Johnson went on to become a leading professor of agricultural economics at Michigan State University. At Chicago his professors were among the foremost in the country.They included Frank Knight, Milton Friedman, D. Gale Johnson, John U. Nef, and T. W. Schultz, several future Nobel Prize winners.Also included are notes by Mark Ladenson (also from Michigan State) at Northwestern and from a faculty seminar at MSU on comparative method.
Keywords: Economics -- Study and teaching (Higher); Economics -- Methodology.; Economics -- Research.; elektronické knihy; electronic books